Menghapus Kejahatan Siber dalam Kasus Peretasan Data Pribadi dengan Modus Social Engineering - Muhammad Al Hadad; Ahmad Jamaludin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
In recent years Cybercrime, including social engineering techniques, has become a serious threat in the digital era, requiring comprehensive handling. This discussion outlines the basic concepts of cybercrime, social engineering techniques, and the urgency from legal, regulatory, technological, and public awareness perspectives. Regulations such as Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) are deemed insufficient to address the evolving complexity of cybercrime. Challenges in law enforcement, such as the transnational nature of crimes and limited resources, necessitate stronger regulations and enhanced capacity of law enforcement agencies. On the other hand, the development of advanced cybersecurity technologies, user education, and increased public awareness are crucial steps to prevent cyberattacks. Collaboration between government, private sector, and society is considered key to creating a secure digital environment. Recommendations include strengthening regulations, investing in security technologies, training IT professionals, and conducting public awareness campaigns. Through a holistic approach, it is hoped that the threat of cybercrime can be effectively minimized.